The Relationship between Primary Education Teachers’ Technological Pedagogical Content Knowledge and Lifelong Learning Tendency - Ertuğrul Çam; Fatih Saltan (Elementary Education Online, 2023)
The aim of this study is to determine the relationship between primary education teachers’ technological pedagogical content knowledge and lifelong learning tendency. In the study, the survey method, one of the qualitative research methods, was used. 357 primary education teachers in Muş, Bulanık participated in this study. The data was collected with “Technological Pedagogical Content Knowledge Scale” developed by Schmidt and others (2009) and adapted to Turkish by Öztürk and Horzum (2011), and with “Lifelong Learning Tendency Scale” developed by Coşkun (2009). According to the research results, the Technological Pedagogical Content Knowledge does not show a meaningful difference according to gender and accommodation unit while it shows a meaningful difference according to branch and school levels. As for the lifelong learning tendency, it does not indicate a meaningful difference according to gender, branch, accommodation unit, and school level. However, a low rate significant relation between the Technological Pedagogical Content Knowledge and lifelong learning tendency was found.